Status of antimicrobial resistance in food animals in Pakistan (2016–2020): A systematic review and meta-analysis. (Journal of Advanced Veterinary and Animal Research, 2025)
Antimicrobial resistance (AMR) is a global public health issue, causing an estimated 1.27 million deaths in 2019. This systematic review and meta-analysis aim to assess the burden of AMR in food animals in Pakistan, identify resistant microbes, and highlight emerging trends in multidrug resistance (MDR). The major databases were searched for articles published between 2016 and 2020 on the prevalence of AMR in food animals in Pakistan. A random-effects model was employed to pool the prevalence of antibiotic-resistant Enterobacteriaceae and non-Enterobacteriaceae pathogens. Among 1,145 studies, 35 met the inclusion criteria as evidence of AMR in food animals. Escherichia coli showed the highest resistance to ampicillin (59.5%), ciprofloxacin (49%), oxytetracycline (39%), and chloramphenicol (35%); Salmonella to ampicillin (78.4%), amoxicillin (53.9%), chloramphenicol (40%), tetracycline (39.3%), and ciprofloxacin (39%); Staphylococci to cefoxitin (53.8%) and penicillin (34.8%); and Campylobacter and Klebsiella to ciprofloxacin (50.4% and 83.3%, respectively). MDR was observed in E. coli (12/12 studies), Salmonella (7/10), Staphylococci (3/8), Campylobacter (3/3), and Klebsiella (1/3), with extensive drug resistance in E. coli (3/12), Salmonella (4/10), Campylobacter (1/3), and Klebsiella (2/2). Enterobacteriaceae showed significant resistance to tetracyclines (pooled prevalence/PPr = 0.75) and aminopenicillins (PPr = 0.74), whereas non-Enterobacteriaceae showed resistance to cephalosporins (PPr = 0.67) and aminopenicillins (PPr = 0.59), both with substantial heterogeneity. This review shows the existence of bacteria resistant to commonly used antimicrobials in food animals, potentially a threat to both human and animal health. The findings suggest the continuous monitoring of AMR and antimicrobial use (AMU) and the regulation of AMU in the food and agriculture sectors.J. Adv. Vet. Anim. Res., 12(2): 668–679, June 2025http://doi.org/10.5455/javar.2025.l930